Ultrathin Layers of PdPX (X=S, Se): Two Dimensional Semiconductors for Photocatalytic Water Splitting. Issue 55 (5th September 2017) - Jing, Yu; Ma, Yandong; Wang, Yu; Li, Yafei; Heine, Thomas
Abstract: On grounds of first principles calculations we propose two‐dimensional semiconductors, ultrathin mono‐, bi‐ and trilayers of PdPX (X=S, Se), as photocatalysts with band gaps suitable for harvesting the visible part of the solar spectrum and band edge energies matching the electrochemical potentials required for water splitting reaction. Layered bulk palladium phosphochalcogenides, among them the title compounds, have been known since 1971.1 The cleavage energy of ≈0.6 J m −2 suggests that single and few layer PdPX can be produced by exfoliation from the bulk phase. PdPX monolayer possesses a moderate band gap of 2.12 (1.97) eV for PdPS (PdPSe) and shows high, albeit anisotropic, carrier motilities. Bandgap (and edge) engineering is possible by applying strain (in the range of 1.5∼2.3 eV), and by varying the number of layers, that is, to 1.95(1.80) eV for the bi‐ and 1.75 (1.62) eV for the trilayer, to 1.70 (1.43) eV in the bulk. Abstract : Two‐dimensional semiconductors, ultrathin layers of pyrite‐type PdPX (X=S, Se), can be cleaved from their known layered bulk structure. Due to band gap increase, the electronic properties meet the requirements for photocatalytic water splitting, which is further facilitated by thermal and chemical stability, high carrier mobilities and the presence of catalytically active Pd atoms.